Chemotherapeutic treatment is associated with Notch1 induction in cutaneous T-cell lymphoma. Issue 1 (2nd January 2017) - Kamstrup, Maria R.; Biskup, Edyta; Manfè, Valentina; Savorani, Cecilia; Liszewski, Walter; Wirèn, Johan; Specht, Lena; Gniadecki, Robert
Abstract: The Notch pathway is important for survival of cutaneous T-cell lymphoma (CTCL) cells. We investigated the effect of chemotherapy (doxorubicin, etoposide, and gemcitabine) and radiation modalities on Notch signaling in CTCL cell lines. Chemotherapy induced Notch1 expression at the mRNA and protein level in MyLa2000 and Hut78. Upregulation of well-established Notch targets supported the functional activity of Notch1. Transfection of Notch1 siRNA into MyLa2000 cells was not able to suppress the effects of chemotherapy on Notch1 activation significantly. Notch1 knockdown in combination with doxorubicin, etoposide, or gemcitabine compared to chemotherapy alone decreased cell viability by 12, 20, and 26%, respectively ( p < 0.05). Additionally, X-rays (in MyLa2000 but not SeAx) and psoralen plus UVA (PUVA) (in MyLa2000, Hut78, and SeAx) increased the expression of Notch1 family members. Our results indicate that CTCL cells activate the Notch pathway in vitro in response to chemotherapy and radiation modalities as a possible protective mechanism.